Luzula effusa var. chinensis (Juncaceae): the first record for the wood-rush genus in Vietnam - Ford, Bruce Austin; Vu, Anh Tai; Nguyen, Kim Thanh; Starr, Julian Richard (Phytotaxa, 2015)
Mount Fansipan, situated in the Hoang Lien Son Range, supports a rich subtropical and temperate flora of over 1700 species, including 25% of Vietnam’s endemic plant taxa (Nguyen & Harder 1996, Sterling et al. 2006). At elevations above 2000 m, Mount Fansipan contains numerous temperate genera including Acer Linnaeus (19 spp., Sapindaceae Jussieu), Alnus Miller (A. nepalensis, Betulaceae Gray), Betula Linnaeus (B. alnoides Buchanan-Hamilton, Betulaceae), Carex Linnaeus (36 spp., Cyperaceae Jussieu), Clematis Linnaeus (9 spp., Ranunculaceae Jussieu), Lithocarpus Blume (13 spp., Fagaceae Dumortier), Quercus Linnaeus (9 spp., Fagaceae), Rhododendron Linnaeus (40 spp., Ericaceae Jussieu), Rubus Linnaeus (36 spp., Rosaceae Jussieu), Tsuga Carrière (T. dumosa Eichler, Pinaceae Sprengel ex F. Rudolphi), Ulmus Linnaeus (U. lancifolia Roxburgh, Ulmaceae Mirbel), Vaccinium Linnaeus (12 spp., Ericaceae), and Viola Linnaeus (12 spp., Violaceae Batsch) (Vietnam Plant Data Center 2015, Nguyen & Harder 1996) with many of these genera being both species-rich and locally common (Nguyen & Harder 1996, pers. obs.). In April 2012, a collection of a specimen, representing the temperate genus Luzula de Candolle (1805: 158), was made while conducting botanical studies on the Carex flora of Mount Fansipan, Lao Cai Province, Vietnam, which is about 30 km south of the border with Yunnan Province, China. While the specimen was immediately recognized as a Luzula, a new genus to the flora of Vietnam (Vietnam Plant Data Center 2015), it was not until our collection was identified using the keys in Wu & Clements (2000) and Kirschner (2002) that it was determined to be Luzula effusa Buchenau (1879: 88) (Figs. 1, 2). A Basic Alignment Search Tool (BLAST) search of an internal transcribed spacer region (ITS1+5.8S+ITS2) sequence obtained from our specimen (KM612280) showed a 100% match with an existing sequence for L. effusa var. chinensis (Brown 1903: 161) Wu (1992: 92) (AY727778.1, see Drábková & Vlcek 2010) in GenBank (National Center for Biotechnology Information 2014), supporting our identification based on morphology (Table 1). Eighteen other Luzula accessions, representing species placed in two different subgenera and four different sections, were found to have 100% coverage and 99% identity with the sequence from our specimen (National Center for Biotechnology Information 2014) (Table 1). In all cases, these sequences came from taxa that occur in regions that are more geographically disparate from Vietnam than the previously known closest location for L. effusa (see below). These taxa are also morphologically dissimilar to our specimen (see text below and Table 1).